Key Research Issues in Clostridium difficile. Issue 5 (2005) - Zhanel, George; Hammond, Greg
Abstract : Clostridium difficile is an emerging pathogen that causes C difficile -associated diarrhea, an important nosocomial infection. Control of this infection remains a challenge, and much needs to be determined about the antimicrobial resistance of the organism, antibiotic stewardship, contamination of the patient environment, and various host factors that determine susceptibility or resistance to infection. A national symposium focusing on C difficile infections, the Clostridium difficile Symposium on Emerging Issues and Research, was hosted on November 23, 2004, by the Department of Medical Microbiology and Infectious Diseases at the University of Manitoba, Winnipeg, Manitoba, in partnership with the Canadian Institutes of Health Research. This symposium, which aimed to summarize key research issues regarding C difficile infections in Canada, had the following objectives: to provide a forum for learning and discussion about C difficile and its impact on the health of Canadians; to identify the key research issues that should be addressed; and to explore potential research funding opportunities and collaboration. The present report summarizes key research issues identified for C difficile infections in Canada by addressing four major themes: diagnosis and surveillance, infection prevention and control, antibiotic stewardship, and clinical management.